Sudan Social Safety Net Assessment - Kjellgren, Annika; Jones-Pauly, Christina; El-Tayeb Alyn, Hadyiat; Tadesse, Endashaw; Vermehren, Andrea (World Bank, Washington, DC, 2014)
The Sudanese population has suffered from years of conflict, and deep-seated security issues have severely hampered Sudan s long-term economic stability and social development. As a consequence, Sudan is struggling to meet its MDGs. Since the secession of South Sudan, Sudan has lost a considerable part of its oil production and fiscal revenues. At the same time, the Government recognizes social safety nets as important instruments for reducing poverty. This report provides an analysis of the state of social safety nets in Sudan which shows that Sudan s existing safety net programs are limited in coverage, lack coordination, as well as monitoring and evaluation. The report suggests (i) reallocation of savings from the fuel subsidy reform to targeted pro-poor safety net programs; (ii) strengthening of the existing safety net through monitoring the outcomes, strong controls and social accountability, and a culture of evaluation, and (iii) development of a coherent National Social Protection Policy.